Pertobatan di Dalam Philokalia: Artikel Ulasan - Hendi Wijaya (Sekolah Tinggi Teologi Intheos Surakarta, 2018)
Abstract. This is a review article of repentance according to the writers of Philokalia. Philokalia is a collection of texts written between the fourth and fifteenth centuries by monks and Church Fathers from the Orthodox Christian tradition. Repentance is a process of renewing the inner man with tears so that the outer man is being process of holy before God and mature in Christ. There are two main points of the review: the process of repentance and the results of repentance. The process of repentance is the renewal of NOUS to Christ's maturity so that our NOUS or the intellect is not subject to the body or the desires of the flesh. The result of repentance is the sanctity of life and baptism in truth.Abstrak. Artikel ini adalah sebuah ulasan tentang pertobatan menurut pandangan para Bapa Gereja dalam buku Philokalia. Philokalia adalah kumpulan teks yang ditulis antara abad keempat sampai kelima belas oleh para rahib dan Bapa Gereja dalam tradisi Kristen Ortodoks. Pertobatan adalah suatu proses pembaruan manusia batiniah dengan air mata sehingga manusia lahiriah kembali menjadi kudus di hadapan Allah menuju kedewasaan ke arah Kristus. Ada 2 hal pokok pembahasan yaitu proses pertobatan dan hasil pertobatan. Proses pertobatan adalah pembaruan NOUS menuju kedewasaan seperti Kristus sehingga NOUS atau the intellect kita tidak takluk pada tubuh atau keinginan daging. Hasil pertobatan adalah kesucian hidup di dalam kebenaran dan pengudusan baptisan.